Sistem Informasi Pengaduan Masyarakat Berbasis Website - Megadana, I Putu Krisna Krisna; Cahyadi Putra, I Gusti Ngurah Anom (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 2 No 1 (2023): JNATIA Vol. 2, No. 1, November 2023DO - 10.24843/JNATIA.2023.v02.i01.p09, 2023)
Public complaints are an important mechanism in maintaining accountability of the government and other organizations, as well as strengthening relations between the government and citizens. Public complaints provide an opportunity for individuals or groups to report problems, dissatisfaction, or violations they experience related to public services, corruption, human rights violations, and so on. However, in some cases in some areas it is still difficult to make complaints about the environment that occur in the community. Therefore, we have compiled this journal with the title "Website-based public complaint information system" to help the public in making complaints against local governments. The information system has of course become a very integral tool for human life, therefore the existence of a "website-based public complaint information system" can help the public easily.